Spinning Hopf solitons on S3 × ℝ - Do Bonfim, André Correia Risério [UNESP]; Ferreira, Luiz Agostinho [UNESP] (Springer Nature, 2006)
We consider a field theory with target space being the two dimensional sphere S2 and defined on the space-time S3 × . The Lagrangean is the square of the pull-back of the area form on S2. It is invariant under the conformal group SO(4,2) and the infinite dimensional group of area preserving diffeomorphisms of S2. We construct an infinite number of exact soliton solutions with non-trivial Hopf topological charges. The solutions spin with a frequency which is bounded above by a quantity proportional to the inverse of the radius of S3. The construction of the solutions is made possible by an ansatz which explores the conformal symmetry and a U(1) subgroup of the area preserving diffeomorphism group. © SISSA 2006.
Keywords: Integrable Field Theories; Integrable Hierarchies; Sigma Models